INSTITUTIONAL AND ORGANIZATIONAL-ECONOMIC MECHANISMS FOR ENSURING SUSTAINABLE ECONOMIC GROWTH IN AGRICULTURE - Qushoqov Fakhriddin Bakhtiyorovich (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to explore the institutional and organizational-economic mechanisms that underpin innovative agro-digital growth within the framework of sustainable agricultural development in Uzbekistan. Method: Using a qualitative and analytical approach, the research synthesizes institutional reforms, economic modernization, and digital transformation initiatives—such as Agriculture 4.0 and cluster-based management—to evaluate their combined impact on sustainability and competitiveness in the agricultural sector. Results: The analysis reveals that sustainable agricultural growth depends on the synergistic interaction among institutional reforms, digitalization, and innovation transfer systems, leading to enhanced productivity, rural development, and social equity. The findings highlight that balancing economic efficiency, environmental protection, and social inclusiveness is critical for long-term agricultural sustainability. Novelty: This study introduces an integrative framework that connects institutional and organizational-economic mechanisms with digital and cluster-based models, offering a replicable approach for developing adaptive policies that promote economic, ecological, and social resilience in emerging agri-economies.